Norovirus GII.4 antibodies in the Portuguese population - João Rodrigo Mesquita; Maria São José Nascimento (Journal of Infection in Developing Countries)
Introduction: Norovirus GII.4 is the leading cause of outbreaks of acute and sporadic acute gastroenteritis worldwide. Information on the prevalence of norovirus in Portugal is scarce or null. Methodology: We used a GII.4 norovirus virus-like particle-based enzyme immune assay to measure the seropositivity rate of GII.4 norovirus. Results: A total of 342 (70%) out of 473 serum samples tested positive for anti-GII.4 norovirus IgG. No statistically significant differences were found between regions, sex and age groups. Conclusion: Norovirus GII.4 infections are frequent in Portugal.